Encapsulation of p-Acetylarsenazo in Nanoscale MCM-41 - Zou, Ming-Qiang; Xue, Yu; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2010)
MCM-41 molecular sieve was prepared in alkaline medium by using cetyltrimethylammonium bromide as template, tetraethoxysilane (TEOS) as silica resource. Guest material p-acetylarsenazo (ASApA) was incorporated into the molecular sieve host to obtain host-guest nonacomposite materials (MCM-41)-ASApA. Chemical analysis showed that p-acetylarsenazo has entered in the MCM-41 host. The powder X-ray diffraction test results indicated that the ordered degrees of the MCM-41 in the host-guest nanocomposite materials were still remained good and the frameworks of the molecular sieves were not destroyed by the incorporation of the p-acetylarsenazo. The low-temperature nitrogen adsorption-desorption results at 77 K showed that the surface area and the pore volume of the post-encapsulation host-guest nanocomposite materials were decreased compared to those of the unincorporated host molecular sieves, indicating that the guest has partially occupied the channels of the molecular sieves. The scanning electron microscopic studies indicated that the (MCM-41)-ASApA particles presented spherical and have a size of 115 ± 10 nm for the sample containing 2.93 % of p-acetylarsenazo. Raman spectra showed that the frameworks of the host molecular sieves of the prepared host-guest nanocomposite materials were kept intact. The ultraviolet-visible solid state diffuse reflection absorption spectra indicated that the absorptions of the host-guest nonacomposite materials prepared had obvious blue-shifts compared with that of the guest material, proving that the guest dye had already incorporated into the channels of the molecular sieves. The luminous spectra showed that the post-encapsulation host-guest composite materials have the character of luminescence at 466 nm. The host-guest composite materials (MCM-41)-ASApA have potential use in the domain of sensor, light-emitting devices and laser part materials.